(untitled) (Journal of Bangladesh Institute of Planners, 2025)
The escalating frequency of riverbank erosion in Bangladesh has led to a marked increase in the number of internally displaced persons (IDPs) who are deprived of essential services such as adequate housing, employment, healthcare, and security. In response, various interventions have been implemented by government bodies, private sectors, and non - governmental organizations to mitigate the impacts of displacement. A notable recent initiative is the countrywide Ashrayan-2 project, targeting the rehabilitation of the landless- homeless people with a vision to uplift their livelihoods. As a representative sample of those eligible for resettlement, the IDPs’ challenges are examined in this study, followed by an assessment of interventions in the Ashrayan Project in a riverbank erosion context. Employing Participatory Rural Appraisal (PRA) techniques and the Sustainable Livelihoods Framework (SLF), this qualitative research shows the issues that the Ashrayan-2 project addressed and those that were not. The findings of this study offer insights and recommendations for future interventions and resettlement project design , considering the needs and challenges of IDPs and current project beneficiaries. JBIP, Vol. 17, 2024, pp. 101-118